2012
DOI: 10.1002/bin.1348
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Response Interruption and Redirection (Rird) and Differential Reinforcement on Vocal Stereotypy and Appropriate Vocalizations

Abstract: The relation between contextually appropriate vocalizations (AV) and vocal stereotypy (VS) has yet to be established within the response interruption and redirection (RIRD) literature. RIRD may promote AV by suppressing VS and/or by functioning as incompatible responses. The occurrence of VS and AV was assessed during baseline, RIRD alone, and RIRD combined with a differential reinforcement system for AV (RIRD + DRI) for a 5-year-old child with autism. Results showed an increase in AV once RIRD was implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 11 publications
1
27
1
Order By: Relevance
“…These results are consistent with previous findings (Ahrens et al, 2011) that suggest that the topography of the demands is not a significant variable in the effectiveness of RIRD. It is possible that vocal demands presented during VRIRD generated (vocal) responses that were incompatible with vocal stereotypy (Ahearn et al, 2007;Dickman et al, 2012). However, VRIRD did not seem to be more effective than MRIRD across participants.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These results are consistent with previous findings (Ahrens et al, 2011) that suggest that the topography of the demands is not a significant variable in the effectiveness of RIRD. It is possible that vocal demands presented during VRIRD generated (vocal) responses that were incompatible with vocal stereotypy (Ahearn et al, 2007;Dickman et al, 2012). However, VRIRD did not seem to be more effective than MRIRD across participants.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, this method of data collection may not have captured every occurrence of vocal stereotypy. As responses to vocal demands may directly compete with vocal stereotypy, it is possible that VRIRD would have been found to be more effective than MRIRD (Dickman et al, 2012). It would be beneficial for future studies comparing both procedures to formally report on vocal stereotypy across treatment and non-treatment times as suggested by Martinez and Betz (2013).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Both vocal RIRD and motor RIRD were effective in reducing the level of vocal stereotypy for all four subjects without the requirement of compliance with instructions. RIRD has also been evaluated as a component of larger treatment packages in several studies (Athens, Vollmer, Sloman, & St. Peter Pipkin, 2008;Col on, Ahearn, Clark, & Masalsky, 2012;Dickman, Bright, Montgomery, & Miguel, 2012;Love, Miguel, Fernand, & LaBrie, 2012;Miguel, Clark, Tereshko, & Ahearn, 2009).…”
mentioning
confidence: 99%
“…As a result, exclusion of vocal stereotypy that occurs during the RIRD intervention may underestimate the overall level of vocal stereotypy across the entire session. Although a few studies have reported the total level of vocal stereotypy during sessions, including that which occurred during the intervention (e.g., Athens et al, 2008;Carroll & Kodak, 2014;Schumacher & Rapp, 2011), most studies have replicated the data-collection and analysis procedures used by Ahearn et al (2007) and did not report data on vocal stereotypy that occurred during the intervention (Ahrens et al, 2011, Experiment 1;Col on et al, 2012;Dickman et al, 2012;Liu-Gitz & Banda, 2009;Love et al, 2012;Miguel et al, 2009). This method of analyzing data may overestimate the efficacy of RIRD as a treatment procedure.…”
mentioning
confidence: 99%